Pragmatizmus és megkerülés, avagy hogyan sajátította ki Richard Rorty a dekonstrukciót? - Csató, Péter (Studia Litteraria, 2016)
Jacques Derrida and Richard Rorty are often seen as forming a philosophical kinship, on account of their shared skepticism about the metaphysical tradition and the hegemony of positivist reason. It is all the more confounding, therefore, that in Rorty’s readings of Derrida, we find a frequently recurring argument to the effect that Derrida had best withdraw from the critique of the metaphysical tradition. Metaphysical problems, Rorty explains, are obsolete, no longer relevant to the purposes of expedient inquiry, thus they ought to be circumvented rather than overcome. The statement is rather perplexing insofar as Rorty himself seems to be engaged in such critique throughout his oeuvre. In my paper, I attempt to explicate Rorty’s apparently contradictory statement on rhetorical rather than conceptual grounds. I argue that the contradiction gets resolved once we assume that introducing the notion of circumvention is a rhetorical ploy on Rorty’s part, which serves to dissociate Derrida from his (Rorty’s) own critical project, and thereby appropriate his position.